Analysis of the hyperfine structure of the Cs233Σg+ state. (July 2020) - Onishchenko, Sofiia S.; Sovkov, Vladimir B.; Xie, Feng; Li, Dan; Lukashov, Sergey S.; Baturo, Vera V.; Wu, Jizhou; Ma, Jie; Li, Li
Highlights: Hyperfine structures in 52 spectra of the cesium dimer observed with the PFIIDR experimental technique are analyzed for the first time. The theoretical physical model is proposed, which describes all stages of the excitation-deexcitation scheme of the experiment. The nonadiabatic coupling of all component of the window PFIIDR states is taken into account completely. The parameters of the fine and hyperfine interactions are determined and reported. The results of the experimental spectra simulation are presented. Graphical abstract: Abstract: We report on theoretical calculations and analyses of the hyperfine structures in the spectra of the Cs2 3 3 Σ g + state observed by Li et al by infrared-infrared (IR-IR) double resonance spectroscopy in 2008. For this purpose, we consider the excitation–de-excitation schemes in their entirety, taking into account the mixed character of the intermediate levels of the A 1 Σ u + ∼ b 3 Π Ω u system, which generally contains contributions from all Ω = 0, 1, 2 basis states. We also avoid an approximation for the strongest features in the spectra (the major component), in which the probabilities of optical dipole transitions are computed from 0-th order state vectors alone. We compute the contributions from all components of the mixed states. The fundamental theory and algorithms are described, the parameters of the chosen model are fitted and reported, and the results of the simulation are presented.